2020
DOI: 10.21203/rs.3.rs-53999/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Validation of Conventional Non-Invasive Fibrosis Scoring Systems in Patients with Metabolic Associated Fatty Liver Disease

Abstract: Background:Non-invasive fibrosis scores are not yet validated in the newly defined metabolic associated fatty liver disease (MAFLD). This study evaluated the diagnostic performance of four non-invasive scores including AST to platelet ratio index (APRI), fibrosis-4 index (FIB-4), BMI, AST/ALT ratio, and diabetes score (BARD), and NAFLD fibrosis score(NFS) in patients with MAFLD.Methods: Consecutive patients with histologically-confirmed MAFLD were included. The discrimination ability of different non-invasive … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“… 62 Of the non-invasive blood tests, FIB-4 and NFS mostly outperformed the other scoring systems (namely, APRI and BARD, which stands for BMI, AST/ALT ratio and presence of T2DM) for both MAFLD and NAFLD. 63 , 64 Even though these two tests can be used with confidence in overweight, obese and severely obese patients, their performance in lean and morbidly obese patients was found to be questionable. 65 …”
Section: How: Steps Towards Appropriate Screening In At-risk Populationmentioning
confidence: 99%
“… 62 Of the non-invasive blood tests, FIB-4 and NFS mostly outperformed the other scoring systems (namely, APRI and BARD, which stands for BMI, AST/ALT ratio and presence of T2DM) for both MAFLD and NAFLD. 63 , 64 Even though these two tests can be used with confidence in overweight, obese and severely obese patients, their performance in lean and morbidly obese patients was found to be questionable. 65 …”
Section: How: Steps Towards Appropriate Screening In At-risk Populationmentioning
confidence: 99%
“…68,69 It is generally accepted that FIB-4 and NFS are superior to APRI and BARD in both MAFLD and NAFLD populations. [70][71][72][73] On analyzing a cohort of 417 patients with biopsy-proven MAFLD, Wu et al 70 Although the use of FIB-4 and NFS should be preferred over other panels for the screening of advanced fibrosis, their application in patients with MAFLD is not without limitations. First, their main clinical utility lies in their ability to exclude -rather than identify -advanced fibrosis.…”
Section: Diagnosismentioning
confidence: 99%
“…68,69 It is generally accepted that FIB-4 and NFS are superior to APRI and BARD in both MAFLD and NAFLD populations. 7073 On analyzing a cohort of 417 patients with biopsy-proven MAFLD, Wu et al 70 reported that FIB-4 was characterized by the highest area under curve (0.736; 95% CI: 0.691−0.778) followed by NFS (0.724; 95% CI: 0.679−0.767), APRI (0.671; 95% CI: 0.623−0.715), and BARD (0.609; 95% CI: 0.560−0.656).…”
Section: Diagnosismentioning
confidence: 99%